The divinization of Caesar and Augustus - Koortbojian, Michael. (Cambridge, UK ; New York, NY)
xxiii, 341 sayfa
Keywords: “This book examines the new institution of divinization that emerged as a political phenomenon at the end of the Roman Republic with the deification of Julius Caesar. Michael Koortbojian addresses the myriad problems related to Caesar's, and subsequently Augustus', divinization, in a sequence of studies devoted to the complex character of the new imperial system. These investigations focus on the broad spectrum of forms - monumental, epigraphic, numismatic, and those of social ritual - used to represent the most novel imperial institutions: divinization, a monarchial princeps, and a hereditary dynasty. Throughout, political and religious iconography is enlisted to serve in the study of these new Roman institutions, from their slow emergence to their gradual evolution and finally their eventual conventionalization.” --